2022
DOI: 10.1029/2021sw002891
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Storm‐Induced Ionospheric Irregularities at Equatorial and Middle Latitudes During the 25–26 August 2018 Geomagnetic Storm

Abstract: The 25-26 August 2018 space weather event was classified as the third largest geomagnetic storm of the twenty fourth solar cycle (in terms of the Dst minimum excursion) after the March 2015 and June 2015 geomagnetic storms. The slowly moving coronal mass ejection (CME) occurring on 20 August 2018 was expected to cause a minor geomagnetic activity only, but surprisingly it turned into a strong geomagnetic storm at the very end of the twenty fourth solar cycle. The space weather events of such intensity occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 70 publications
4
30
0
Order By: Relevance
“…The results of our study support that the TEC configuration correlates with irregularities mostly in the low-latitude ionosphere and has a nighttime effect. This is also observed in the results of Cherniak and Zakharenkova, 2022, who observed that nighttime until sunrise irregularities persist at low latitudes.…”
Section: Figure 13supporting
confidence: 76%
“…The results of our study support that the TEC configuration correlates with irregularities mostly in the low-latitude ionosphere and has a nighttime effect. This is also observed in the results of Cherniak and Zakharenkova, 2022, who observed that nighttime until sunrise irregularities persist at low latitudes.…”
Section: Figure 13supporting
confidence: 76%
“…The irregularities manifest as equatorial plasma bubbles (EPBs) in airglow ionospheric images. Electric field perturbations during geomagnetic active periods are reported to enhance (Basu et al, 2010;Cherniak & Zakharenkova, 2022;Kil et al, 2016;Patra et al, 2016;Tulasi Ram et al, 2008;Zakharenkova & Cherniak, 2020) and sometimes inhibit (Aarons, 1991;Abdu et al, 1995;Spogli et al, 2016) the irregularities. Using the AE-parameterized Fejer-Scherliess model for disturbance vertical drifts versus storm time and local time, Martinis et al (2005) were able to summarize these apparently contradictory effects.…”
mentioning
confidence: 99%
“…The equatorial ionospheric perturbations during disturbed conditions are affected by the combined effects of PPEF and DDEF from the high latitude ionosphere. Hence the effect of geomagnetic storms in the context of generation/inhibition of ESF is an important space weather concern and has received a lot of attention in the recent past (Li et al 2018;Cherniak 2022;Zhang et al 2022). Li et al (2018) showed that strong southward IMF Bz excursions during storm rapidly raised the F layer near sunset and led to the development of intense equatorial plasma irregularities.…”
Section: Introductionmentioning
confidence: 99%